Extragalactic stellar tidal streams : Observations meet simulation - Miró-Carretero, Juan; Gómez-Flechoso, María A.; Martínez-Delgado, David; Cooper, Andrew P.; Roca-Fàbrega, Santi ; 0000-0002-6299-152X; Akhlaghi, Mohammad; Pillepich, Annalisa; Kuijken, Konrad; Erkal, Denis; Buck, Tobias; Hellwing, Wojciech A.; Bose, Sownak; et al. (Astronomy and Astrophysics, 2025)
Context. According to the well-established hierarchical framework for galaxy evolution, galaxies grow through mergers with other galaxies. The ΛCDM cosmological model predicts that the stellar halos of massive galaxies are rich in remnants resulting from minor mergers. Stellar Streams Legacy Survey (SSLS) has provided a first release of a catalogue with a statistically significant sample of stellar streams in the local Universe, detected in deep images from DESI Legacy Surveys and Dark Energy Survey (DES). Aims. The main objective is to compare observations of stellar tidal streams from the SSLS catalogue with predictions from state-of-the-art cosmological simulations regarding their abundance, up to a redshift of z < 0.02, according to the ΛCDM model. Methods. In particular, we used the outcome of cosmological simulations from Copernicus Complexio, TNG50 of the IllustrisTNG project, and Auriga to generate mock images of nearby halos and search for stellar streams. We compared the stream frequency and characteristics found in these images, as well as the results of a photometric analysis of the simulations data with DES observations. Results. We found a generally good agreement between the real images and the simulated ones regarding frequency and photometry of streams, while we found differences in the stream morphology between the observations and the simulations, and among the simulations themselves. By varying the sky background of the synthetic images to emulate different surface brightness limit levels, we were also able to obtain predictions for the detection rate of stellar tidal streams up to a surface brightness limit of 35 mag arcsec-2. Conclusions. The cosmological simulations predict that with an instrument akin to the one used in DES, it would be necessary to attain a surface brightness limit of 32 mag arcsec-2 in the r-band to achieve a frequency of up to ∼70% in the detection of stellar tidal streams around galaxies in the redshift range considered here.
Keywords: Cosmology: observations; Dark matter; Galaxies: evolution; Galaxies: halos; Galaxies: photometry